Fluctuation Analysis in a Queue with (L,N)-Policy and Secondary Maintenance. Discrete Time Parameter Process - Alzahrani, M.S.; Dshalalow, J.H. (Электронное моделирование, 2011)
This paper generalizes numerous classes of queues with vacationing servers. In our model, a server not only leaves the system, but he services packets of jobs at a secondary facility up until the total number of single jobs exceeds a specific threshold. The strategy of server processes is represented for different state of queue.We use various techniques (including fluctuation analysis) to deliver explicit formulas for the queueing processwith discrete time parameters.We also utilize some game-theoretic principles (namely sequential games) to efficiently construct our model.